Methods of determining the amputation level of lower extremity, - Kılıç, B., Yücel, A. S., Yaman, Ç., Hergüner, G., Korkmaz, M., (My University, 2014)
Our purpose in this study is to share our experiences and results regarding the determination of amputation level of lower extremity. A total of 21 patients were included in our study, below-knee amputation was applied to 12 patients for diabetic reasons and 9 patients with traumatic reasons. Various methods were used to determine the level. No post-operative complications occurred apart from subcutaneous hematoma, wound detachment and sterile temporary discharge in all patients. Amputation is the surgical removal of a damaged extremity that cannot be repaired together with its bone from the body. The purpose of amputation is to remove infected, injured or nonfunctional extremity in post-reconstruction, to bring the patient’s function to a sufficient level, to protect length and strength of extremity, to maintain balance between the muscles left for a stable extremity, to provide maximum independent free motion, to remove diseased tissue, to reduce morbidity and mortality, to minimize complications, to ensure wound healing and balance of sitting, and to make position and transfers easier. With this purpose, it is highly important to determine the level of amputation correctly. In the study, the reasons and types of amputation in lower extremity and methods of determining level have been expressed.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Method; Amputations of Extremity; Vascular Embolization